4-(N,N-Dimethylamino)pyridine-Embedded Nanoporous Conjugated Polymer as a Highly Active Heterogeneous Organocatalyst - Zhang, Yuan; Zhang, Yong; Sun, Ya Lei; Du, Xin; Shi, Jiao Yi; Wang, Wei David; Wang, Wei (Chemistry : a European journal, 2012)
We report herein for the first time the incorporation of a versatile organocatalyst, 4‐(N,N‐dimethylamino)pyridine (DMAP), into the network of a nanoporous conjugated polymer (NCP) by the “bottom‐up” approach. The resulting DMAP‐NCP material possesses highly concentrated and homogeneously distributed DMAP catalytic sites (2.02 mmol g−1). DMAP‐NCP also exhibits enhanced stability and permanent porosity due to the strong covalent linkage and the rigidity of the “bottom‐up” monomers. As a result, DMAP‐NCP shows excellent catalytic activity in the acylation of alcohols with yields of 92–99 %. The DMAP‐NCP catalyst could be easily recovered from the reaction mixture and reused in at least 14 consecutive cycles without measurable loss of activity. Moreover, the catalytic acylation reaction could be performed under neat and continuous‐flow conditions for at least 536 h of continuous work with the same catalyst activity. Nanoporous catalyst: DMAP‐NCP, a new network nanoporous conjugated polymer containing 4‐(N,N‐dimethylamino)pyridine catalytic moieties, has been constructed by the “bottom‐up” strategy. It shows excellent activity and recyclability in the acylation of alcohols and phenols, even under neat and continuous‐flow conditions (see figure). This study demonstrates the possibility of using DMAP‐NCP as a robust and effective heterogeneous catalyst, especially for practical applications on a large scale.